Lived Experiences of Postpartum Mothers after Mastitis Surgery in Breastfeeding and Infant Care: A Qualitative Study - Yustika Rahmawati Pratami; Wiwit Vitania; Hasnia Hasnia; Eftyaningrum Dwi Wagyu Astutik; Fenska Narly Makualaina (GLOBAL HEALTH SCIENCE GROUP, 2026)
The postpartum period after mastitis surgery is a challenging time for mothers, especially in continuing breastfeeding. Understanding mothers' experiences during this phase is crucial for improving the quality of healthcare and support for breastfeeding mothers. Objective to explore in depth the experiences of postpartum mothers after mastitis surgery when caring for their babies. This study employed a qualitative design with a phenomenological approach. Data were collected through in-depth interviews with postpartum mothers who had undergone mastitis surgery. The total number of research participants was two. The data were analyzed using thematic analysis techniques to identify emerging patterns of experience. Researchers found seven main themes that describe the experiences of post-operative post-mastitis mothers in the breastfeeding process. The experiences of postpartum mothers with mastitis after surgery demonstrate complex challenges, but also demonstrate resilience and strong motivation to continue breastfeeding.